METHODS FOR CHEMICAL RECLAMATION OF MOBILE SOILS AND SANDS USING COMPOSITION FROM LOCAL STRUCTURES - Adizova Nargiza Zamirovna (Galaxy International Interdisciplinary Research Journal, 2021)
At present, large-scale projects are underway all over the world to reduce areas and desert zones in many continents, including the Central Asian states. This is due to a significant deterioration in environmental safety and a reduction in agricultural land, where the population is in poverty from a shortage of food products and the spread of chronic diseases of the lungs, digestive tract, etc. in these regions. Therefore, the problem of surface fixation of mobile soils (STG) and sands (SS) from wind erosion by chemical reclamation followed by phytoreclamation is considered a globally urgent task for each country located between the Karakum and Kizilkum deserts in Central Asia.